Olivenza, daughter of Spain and granddaughter of Portugal - Svobodova, Petra (Romanica Olomucensia, 2016)
The article is dedicated to the problematic status of the region of Olivenza, which is situated on the border between Portugal and Spain. This region was annexed by Spain during the Napoleonic Wars and it was returned to Portugal by the Congress of Vienna. Nevertheless, despite having recognised Portuguese sovereignty in 1817, Spain has never returned it and has administered it since then. Because of this, the border between Spain and Portugal has never been permanently settled and demarcated and Olivenza has represented a subject of dispute up to now. The article gives a brief outline of the Portuguese and Spanish presence in this territory, concentrating mainly on the legal, political, and cultural aspects of this litigation.
Keywords: Olivenza; Portugal; Spain; litigation; border.